The relation between childhood adversity and adult obesity in a population-based study in women and men - Toni Fleischer (Nature Portfolio, 2021)
Abstract Childhood maltreatment has been shown to relate to adult obesity. In this epidemiological study, we investigate the association between childhood maltreatment and waist-to-height-ratio (WHtR) in a sample of the German adult population, comprising of N = 2936 participants. WHtR, an indicator for risk of obesity, was the primary outcome. Childhood maltreatment was assessed by the Childhood Trauma Screener (CTS), which assesses emotional and physical neglect, abuse as well as sexual abuse. Cohort-data were harmonized and analyzed within DataSHIELD. We used multivariable regression models to estimate the association of childhood maltreatment and WHtR at different levels of adjustments for potential confounders. Overall childhood maltreatment was associated with a higher WHtR in both sexes (women: p = 0.004, men: p < 0.001); associations were no longer significant in women after adding socioeconomic variables, but remained significant in men (p = 0.013). Additionally, we were able to identify sex specific patterns for childhood maltreatment predicting the WHtR. Emotional neglect and abuse had stronger impacts on the WHtR in women than in men, whereas physical neglect and abuse had stronger impacts in men. To our knowledge, this is the first comprehensive population-based study testing various types of childhood maltreatment with WHtR in sex-, region- and weight-stratified analyses. Future studies in clinical populations are warranted to examine U-shaped correlations between increased WHtR and childhood maltreatment.